2007
DOI: 10.1042/bj20061136
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage preference distinguishes the two-component NS2B–NS3 serine proteinases of Dengue and West Nile viruses

Abstract: Regulated proteolysis of the polyprotein precursor by the NS2B-NS3 protease is required for the propagation of infectious virions. Unless the structural and functional parameters of NS2B-NS3 are precisely determined, an understanding of its functional role and the design of flaviviral inhibitors will be exceedingly difficult. Our objectives were to define the substrate recognition pattern of the NS2B-NS3 protease of West Nile and Dengue virises (WNV and DV respectively). To accomplish our goals, we used an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 50 publications
5
84
4
Order By: Relevance
“…WNV NS2B/3 has been shown to preferentially cleave sites with a K at P2, whereas DENV NS2B/3 most efficiently cleaves sites with an R at this position. In contrast, WNV and DENV NS2B/3 proteases both preferentially cleave sites with an R over a K at the P1 position (25,33,62). These studies have indicated that WNV NS2B/3 has a strict preference for G at both the P1= and P2= positions, while DENV NS2B/3 is less selective and can cleave substrates with almost any amino acid at P1= and P2= (33).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…WNV NS2B/3 has been shown to preferentially cleave sites with a K at P2, whereas DENV NS2B/3 most efficiently cleaves sites with an R at this position. In contrast, WNV and DENV NS2B/3 proteases both preferentially cleave sites with an R over a K at the P1 position (25,33,62). These studies have indicated that WNV NS2B/3 has a strict preference for G at both the P1= and P2= positions, while DENV NS2B/3 is less selective and can cleave substrates with almost any amino acid at P1= and P2= (33).…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, cleavage of the WNV C protein was efficient with any of the three residues at the P1= position. This fine specificity was not predicted by studies with recombinant NS2B/3 protease and short peptide substrates (33). We found that the sensitivity of WNV NS2B/3 to changes at the P1= position could be altered when residues at the P6 to P2 and P2= to P4= positions were mutated in various combinations.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…55 The used peptides were deduced from the cleavage sites in the immature WNV polyprotein and are summarized in Table 1.1. showing also the cleavage efficacies in percentage. (73) These data showed the preference of the NS2B-NS3 protease for substrates containing arginine as P1 residue, whereby one sequence with lysine in the NS2A protein was also accepted.…”
Section: Substrate Recognition Site Of the Ns2b-ns3 Proteasementioning
confidence: 99%